Mg Alloy Rod Strengthened by Combined Processes of Deformation-Restricted Forging and Extrusion - Miura, H.; Oba, Y.; Watanabe, C.; Benjanarasuth, T. (My University, 2024)
A new method for strengthening Mg alloy rod is proposed. AZ80Mg alloy rods were forged along the longitudinal axis (LA) at extremely high pressures beyond fracture stress under a condition where plastic deformation was eliminated in a die, i.e., deformation-restricted forging (DRFing), followed by cold extrusion. Although the ultimate tensile strength (UTS) and hardness were gradually raised with DRFing stress, the yield strength (YS) was lowered by sharp basal texture evolution on the plane normal to the LA and tensile axis. However, the extrusion after DRFing drastically changed the texture to (0001) LA, causing a large increase in YS. Consequently, a superior balance of mechanical properties: YS of 376 MPa, UTS of 417 MPa, and ductility of 10%, could be achieved after the combined processes of DRFing and extrusion.
Keywords: DRF; forging; magnesium; mechanical property; microstructure; rod; twin